Chapter 9 Pathways from Ageism to Loneliness (2018)
Many older adults in our society suffer from loneliness – a painful, distressing feeling arising from the perception that one’s social connections are inadequate. When loneliness is experienced over prolonged periods of time, it can become devastating to older adults’ physical and mental health. Loneliness has been associated with depression, cognitive decline, and mortality. As the ageing population around the world grows in size and proportion, tackling late life loneliness is becoming a top priority in both ethical and economic terms. Previous studies have attempted to attribute late life loneliness to individual (micro) and social network (meso)-level characteristics. We argue that ageism at the societal (macro)-level – encompassing stereotypes, prejudices, and de facto discrimination against older adults – predisposes the older population to neglect, social isolation, and ultimately, loneliness. We propose three mechanisms whereby ageism may contribute to loneliness. First, chronic social rejection may incline older adults to avoid and withdraw from social participation. Second, individuals may self-embody the stereotypes of old age such as old age being a time of loneliness. The last path is an objective one, which emphasizes age-based discriminatory practices that increase social exclusion of older adults thereby increasing their risk of becoming lonely.